hiPSC-neurons recapitulate the subtype-specific cell intrinsic nature of susceptibility to neurodegenerative disease-relevant aggregation - Ian Weidling; Christina N. Preiss; Sarah E. Chancellor; Gyan Srivastava; Lauren Gibilisco; Gen Lin; Melanie Shackett Brennan; Janice Lee; Lindsay M. Roth; Olga Morozova; Kyong Nyon Nam; Nehal R. Patel; et al. (Acta Neuropathologica Communications)
Abstract Alzheimer’s disease (AD) is characterized by the accumulation and spread of Tau intraneuronal inclusions throughout most of the telencephalon, leaving hindbrain regions like the cerebellum and spinal cord largely spared. These neuropathological observations, along with the identification of specific vulnerable sub-populations from AD brain-derived single nuclei transcriptomics, suggest that a subset of brain regions and neuronal subtypes possess a selective vulnerability to Tau pathology. Given the inability to culture neurons from patient brains, a disease-relevant in vitro model which recapitulates these features would serve as a critical tool to validate modulators of vulnerability and resilience. Using our recently established platform for inducing endogenous Tau aggregation in human induced pluripotent stem cell (hiPSC)-derived cortical excitatory neurons via application of AD brain-derived exogenous Tau aggregates, we explored whether Tau aggregates preferentially induce aggregation in specific neuronal subtypes. We compared Tau seeding in hiPSC-derived neuron subtypes representing regional identities across the forebrain, midbrain, and hindbrain. Higher susceptibility (i.e. more Tau aggregation) was consistently observed among cortical neuron subtypes, with CTIP2-positive, somatostatin (SST)-positive cortical inhibitory neurons showing the greatest aggregation levels across hiPSC lines from multiple donors. hiPSC-neurons also delineated between the disease-specific vulnerabilities of different protein aggregates, as α-synuclein preformed fibrils showed an increased propensity to induce aggregates in midbrain dopaminergic (mDA)-like neurons, mimicking Parkinson’s disease (PD)-specific susceptibility. Aggregate uptake and degradation rates were insufficient to explain differential susceptibility. The absence of a consistent transcriptional response following aggregate seeding further indicated that intrinsic neuronal subtype-specific properties could drive susceptibility. The present data provides evidence that hiPSC-neurons exhibit features of selective neuronal vulnerability which manifest in a cell autonomous manner, suggesting that mining intrinsic (or basal) transcriptomic signatures of more vulnerable compared to more resilient hiPSC-neurons could uncover the molecular underpinnings of differential susceptibility to protein aggregation found in a variety of neurodegenerative diseases.